The facile construction of a yolk–shell structured metal–TiO2 nanocomposite with potential for p-nitrophenol reduction. (12th February 2018) - Lin, Xi-Jie; Sun, Tian-Qi; Sun, Yong-Gang; Zeng, Chen; Lu, Rong-Wen; Cao, An-Min
Abstract : A versatile synthesis method was developed for the construction of a yolk–shell structured metal–TiO2 nanocomposite. Abstract : A yolk–shell structured metal–TiO2 nanocomposite was constructed using a facile and versatile method. Due to the dual functions of 3-aminophenol which worked as the template precursor and metal ion coordination agent, metal nanoparticles could disperse well, and the as-prepared yolk–shell Ag–TiO2 nanocomposite showed promising catalytic activity for the reduction of p -nitrophenol.